2017
DOI: 10.19044/esj.2017.v13n10p417
|View full text |Cite
|
Sign up to set email alerts
|

Exports as a Determinant of Inflation in Kenya: Disaggregated Econommetric Analysis

Abstract: The purpose of this study was to examine exports as a determinant of inflation in Kenya: A disaggregated econometric analysis with specific objectives of establishing the relationship between domestic exports and inflation in Kenya and determining the relationship between re -exports and inflation in Kenya. This was occasioned by inconclusive and incomprehensive analysis on the relationship between exports and inflation given mixed results and failure by scholars to disaggregate total exports into domestic exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…Manufacturing stands out as one pertinent consideration for the Kenyan government to reduce the rate of exportation. The findings by Kiganda et al [22] support the outcomes of the above studies, including Nyoni [13], Murunga & Mugambi, [21] and Banerjee [10] by suggesting the need to initiate the strategies that can enhance the manufacturing sector in the country as a strategy to reduce inflation.…”
Section: Empirical Literature Reviewmentioning
confidence: 54%
See 1 more Smart Citation
“…Manufacturing stands out as one pertinent consideration for the Kenyan government to reduce the rate of exportation. The findings by Kiganda et al [22] support the outcomes of the above studies, including Nyoni [13], Murunga & Mugambi, [21] and Banerjee [10] by suggesting the need to initiate the strategies that can enhance the manufacturing sector in the country as a strategy to reduce inflation.…”
Section: Empirical Literature Reviewmentioning
confidence: 54%
“…One of the indicators of advancement in the manufacturing sector is the country's exportation rate. Subsequently, Kiganda, Obange, and Adhiambo [22] conducted a study aimed at identifying the effect of exports on inflation in Kenya using monthly series data between January 2005 and December 2015 (132 months). Findings indicated a significant positive relationship between export and inflation.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…The increase in exports had exacerbated the supply-demand gap which triggered inflation in Pakistan, and thus they suggested that more focus should be put on meeting domestic demand and using resources wisely to boost production. Correlation analysis performed by Kiganda et al [19] revealed a weak significant association between re-exports and inflation, but a strong significant correlation between domestic exports and inflation in Kenya. The Johansen co-integration test showed that domestic exports had highly influenced the inflation in Kenya, whereby they had a significant positive long-run relation.…”
Section: Empirical Findingsmentioning
confidence: 94%